Severe Hypocalcemia due to Vitamin D Deficiency after Extended Roux-en-Y Gastric Bypass - I. Miñambres; A. Chico; A. Pérez (Hindawi Limited, 2011)
Vitamin D deficiency is a well-known comorbidity of obesity that can be exacerbated after bariatric surgery and can predispose the patient for hypocalcemia. Vitamin D and calcium doses to prevent and treat vitamin D deficiency after weight loss surgery are not well defined. We describe a patient who developed severe hypocalcemia due to vitamin D deficiency 5 years after an extended Roux-en-Y gastric bypass for a type II obesity. No precipitating factors were present and malabsorption induced by the bypass was considered to be the main causative factor. High doses of vitamin D and calcium were needed to reach and maintain normal calcium and vitamin D concentrations. This case emphasises the importance of routine screening for vitamin D deficiency in obese individuals and reflects that while consensus does not exist regarding optimal dosage, vitamin D replacement should be tittered based on calcidiol levels.